Factors associated with early mycological clearance in HIV-associated cryptococcal meningitis. - Fátima Concha-Velasco; Elsa González-Lagos; Carlos Seas; Beatriz Bustamante (PLoS ONE, 2017)
INTRODUCTION:The first-line combination therapy for HIV-associated cryptococcal meningitis (CM), a condition of high mortality particularly in the first two weeks of treatment, consists of amphotericin B plus flucytosine (5-FC). Given that 5-FC remains unavailable in many countries, the knowledge of factors influencing mycological clearance in patients treated with second-line therapy could contribute to effective management. OBJECTIVES:To determine the factors associated with the clearance of Cryptococcus sp. from the cerebrospinal fluid by the second week of effective antifungal therapy (early mycological clearance) in HIV-associated CM. METHODS:Retrospective cohort study based on secondary data corresponding to HIV-associated CM cases hospitalized at a tertiary health care center in Lima, Peru where 5-FC remains unavailable. Risk factors associated with early mycological clearance were analyzed by generalized linear regression models. RESULTS:From January 2000 to December 2013, 234 individuals were discharged with a diagnosis of HIV-associated CM; in 215 we retrieved the required data. The inpatient mortality was 20% (43/215), 15 of them in the first two weeks of treatment. In the final model (157 cases), adjusted for age, previous episode of CM, ART use, type of antifungal treatment, raised intracranial pressure, frequency of therapeutic lumbar punctures, baseline fungal burden and treatment period, the factors associated with early mycological clearance were: Amphotericin B deoxycholate plus fluconazole as combination therapy (RR, 1.56; 95% CI, 1.14-2.14); severe baseline intracranial pressure (≥35 cm H2O) (RR, 0.57; 95% CI, 0.33-0.99); and baseline fungal burden over 4.5 log10 CFU/mL (RR, 0.61 95% CI: 0.39-0.95). CONCLUSIONS:In a setting without access to first-line therapy for CM, the combination therapy with amphotericin B deoxycholate plus fluconazole was positively associated with early mycological clearance, while high fungal burden and severe baseline intracranial pressure were negatively associated, and thus related to failure.